Loess encounters of three kinds: Charles Lyell talks about, reads about, and looks at loess - Smalley, Ian; Kels, Holger; Gaudenyi, Tivadar; Jovanovic, Mladjen (Instytut Geologii UAM, 2016)
Charles Lyell (1797–1875) was an important loess pioneer. His major contribution was to distribute information on the nature and existence of loess via his influential book ‘The Principles of Geology’. He was obviously impressed by loess when he encountered it; the initial encounter can be split into three phases: conversations about loess; confronting the actual material in the field; and reading about loess in the literature. Detail can be added to an important phase in the scientific development of the study of loess. Significant events include conversations with Hibbert in 1831, conversations and explorations with von Leonhard and Bronn in 1832, the opportunity to include a section on loess in vol. 3 of ‘Principles’ for publication in 1833, a substantial Rhineland excursion in 1833, the reporting of the results of this excursion in 1834, discussions at the German Association for the Advancement of Science meeting in Bonn in 1835. Of all the people encountered perhaps H.G. Bronn was the most significant. Lyell eventually listed eleven people as relevant to the loess writings: Bronn, von Leonhard, Boue, Voltz, Steininger, Merian, Rozet, Hibbert, Noeggerath, von Meyer, Horner – of these Bronn, von Leonhard, Hibbert and Horner appear to have been the most significant, viewed from 2015.
Keywords: Loess; loess history; Charles Lyell; Bronn and Horner